2007
DOI: 10.1097/brs.0b013e318107674e
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Donor Site Pain After Bone Graft Harvesting From the Posterior Iliac Crest May Be Overestimated

Abstract: Patients probably cannot differentiate between donor site pain and residual low back pain. The reported incidence of pain related to posterior iliac crest bone graft harvesting may therefore be overestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 14 publications
1
47
0
8
Order By: Relevance
“…In contrast, Shamsaldin et al [84] demonstrated that after harvesting bone from the iliac crest for 1-level ACDF, 92% had no persisting pain after 1 year. Likewise, in a series on thoracolumbar fractures Delawi et al [22] reported donor site pain in 14%, but 'pain' on a VAS averaged 1.6 only [22]. Our findings concur with that of Delawi and Shamsaldin with the patients' iliac crest related pain averaging only 0.5 on a VAS.…”
Section: Complicationssupporting
confidence: 89%
“…In contrast, Shamsaldin et al [84] demonstrated that after harvesting bone from the iliac crest for 1-level ACDF, 92% had no persisting pain after 1 year. Likewise, in a series on thoracolumbar fractures Delawi et al [22] reported donor site pain in 14%, but 'pain' on a VAS averaged 1.6 only [22]. Our findings concur with that of Delawi and Shamsaldin with the patients' iliac crest related pain averaging only 0.5 on a VAS.…”
Section: Complicationssupporting
confidence: 89%
“…Tantalum has the advantage that it avoids donor-site morbidity of harvesting the iliac crest graft and the possibility of disease transmission. Harvesting autograft at the iliac crest has a reported donorsite morbidity rate of 15% to 48% (postoperative hematoma, infection, hypesthesia, increased postoperative pain, wound dehiscence, cosmetic defect, prolonged pain in the long term, and impairment in ambulation, work, and activities of daily living [17,21,24,38,42]). The cost of tantalum (approximately $1000 per block in the US) is comparable to allograft ($850, plus approximately [3,4,56] Similar to gold standard [19,54] Difficult radiographic assessment of fusion [28,51,54] No donor-site morbidity, no reported complications [19,20,36,37,54] Unlimited Approximately $1000 per piece 5 minutes of preparation time in the operating theater) or harvesting iliac crest autograft (estimated at $600 to $700, as it involves approximately 20 minutes of operating time, suture material, sponges, and dressing) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Recognized options currently include autograft, allograft, and xenograft bone, each associated with certain disadvantages. Autograft, which is considered the gold standard for bone grafting because of its high healing potential, is associated with donor-site morbidity in 15% to 48% [17,21,24,38,42,45], postoperative complications (hematoma, hypoesthesia, wound dehiscence) in 3% to 39% [24,38,42], limited quantity, and risk of graft collapse [24]. Allograft and xenograft carry the risk of infectious disease transmission, lower stability attributable to the preparation process, and potential failure to integrate, which can result in graft collapse and failure of surgery [6,24,35].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the incidence of donor-site pain is significantly increased in lumbar or lumbrosacral spinal surgery compared with cervical or thoracic surgery [7,8,15,17]. One group has suggested that this is due to the inability of the patient to differentiate donor-site from primary surgery site pain [15]. Other authors have suggested this phenomenon is due to biomechanical implications of destabilizing the pelvis in patients receiving lumbrosacral fusions [7,8].…”
Section: Discussionmentioning
confidence: 94%
“…Numerous, uncontrolled, retrospective studies have reported their incidence of persistent donor-site pain and it has now been widely accepted to be common, occurring in one-third of patients undergoing autogenous harvest from the iliac crest [5,6,8,10,11,[13][14][15][16][17][18][19]. Some studies have shown that the incidence of donor-site pain is significantly increased in lumbar or lumbrosacral spinal surgery compared with cervical or thoracic surgery [7,8,15,17]. One group has suggested that this is due to the inability of the patient to differentiate donor-site from primary surgery site pain [15].…”
Section: Discussionmentioning
confidence: 99%